2022
DOI: 10.1038/s41598-022-10375-w
|View full text |Cite
|
Sign up to set email alerts
|

The coral reef-dwelling Peneroplis spp. shows calcification recovery to ocean acidification conditions

Abstract: Large Benthic Foraminifera are a crucial component of coral-reef ecosystems, which are currently threatened by ocean acidification. We conducted culture experiments to evaluate the impact of low pH on survival and test dissolution of the symbiont-bearing species Peneroplis spp., and to observe potential calcification recovery when specimens are placed back under reference pH value (7.9). We found that Peneroplis spp. displayed living activity up to 3 days at pH 6.9 (Ωcal < 1) or up to 1 month at pH 7.4 (Ωca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
4
1
Order By: Relevance
“…The moderately positive influence of CO 2 on calcification as observed here is in contrast with the response of the majority of marine calcifiers (Kroeker et al, 2013) and reports on the effect of CO 2 on larger benthic foraminifera (Doo et al, 2014). Although other studies have found mixed responses of large benthic foraminifera to elevated pCO 2 /reduced pH (McIntyre-Wressnig et al, 2013;Narayan et al, 2022) and showed that they are able to withstand periodic undersaturated conditions (Charrieau et al, 2022).…”
Section: Changes In Calcificationcontrasting
confidence: 64%
“…The moderately positive influence of CO 2 on calcification as observed here is in contrast with the response of the majority of marine calcifiers (Kroeker et al, 2013) and reports on the effect of CO 2 on larger benthic foraminifera (Doo et al, 2014). Although other studies have found mixed responses of large benthic foraminifera to elevated pCO 2 /reduced pH (McIntyre-Wressnig et al, 2013;Narayan et al, 2022) and showed that they are able to withstand periodic undersaturated conditions (Charrieau et al, 2022).…”
Section: Changes In Calcificationcontrasting
confidence: 64%
“…The moderately positive influence of CO 2 on calcification as observed here is in contrast with the response of the majority of marine calcifiers [ 57 ] and reports on the effect of CO 2 on larger benthic foraminifera [ 58 ]. Although other studies have found mixed responses of large benthic foraminifera to elevated p CO 2 /reduced pH [ 17 , 59 ] and showed that they are able to withstand periodic undersaturated conditions [ 60 ]. Finally, Fujita et al [ 61 ] reported an optimum growth rate for three species of the large, high-Mg/Ca benthic foraminifera, similar to the pattern reported here.…”
Section: Discussionmentioning
confidence: 99%
“…In the dark treatments, this photosynthetic activity cannot counter low pH or low DIC conditions, which could therefore have affected the δ 7 Li values and Li/Ca ratios in the low pH and low DIC treatments. This finding is consistent with a culture study using the LBF Peneroplis spp., in which three days under lower pH and darker conditions were sufficient to affect the geochemical signatures of their tests [58].…”
Section: Effect Of Light Intensitymentioning
confidence: 99%